Agenda Setting Dalam Perencanaan Pembangunan Perbatasan di Kepri Tahun 2015 - Eki Darmawan (Jurnal Selat, 2015)
Bondary not only separate territories that are owned by different communities or countries but also ensure the safety and well-being balanced between each area concerned. Riau Islands Province is leading directly adjacent to neighboring countries such as Malaysia, Singapore the Philippines, and Thailand. Conditions islands region in Riau (Riau Islands) are very much separated by an ocean, the area is 252 601 km2 area consisting of 1,350 islands and 96% Ocean thus making control range of the government in development planning very difficult. This study will look at how the government’s Agenda Setting in the border area development planning Riau Islands, which will discuss the issue and political currents flow in the policy agenda to the policies made by the government of Riau islands as border regions. The method used in this study is qualitative. The study was conducted in Regional Development Planning Board (Bappeda) Riau Islands Province, the Regional Border Management Agency (BNPPD) Riau Islands Province and Commission III of the House of Representatives (DPRD) Riau Islands Province. Data collection techniques performed in this study were interviews, collecting data document written and unwritten, and non-participant observation. Results from this study is the first, the flow of matter to explain the issues and problems that occur on the border of Riau Islands namely the problem of limited infrastructure such as facilities and infrastructure such as facilities and infrastructure of housing, education, health, security, and also facilities and transport infrastructure, telecommunications, and Other causes of this region have low accessibility and isolated from the surrounding region. Secondly, the flow of Politics explains the policy process and then view and objectives to be achieved still has a perception about the construction of the border is still different, the level of public participation, NGOs, academics and NGOs are still relatively low, the handling is still partial, sectoral and yet integritasi, coordination has not gone good, both among sectoral, national level and between the central government and local governments, commitment and development budget in the border area is still relatively minimal. Third, Flow Policy describes several emerging priorities namely, development of processing industry, fishery and tourism in a sustainable manner in order to support the sector of maritime, increasing production and agricultural productivity, as well as self-reliance and food security community, Improved connectivity between regions and between the island and the means and basic infrastructure of society, Improving the quality of the environment and forestry, natural disaster mitigation and climate change, peningatan quality human resources and well-being equitable and civilized society, Improving the quality of public services and good governance. Key words: Agenda Setting, Planning Development, Border